Analisis Relevansi Penanaman Modal Asing, Modal dalam Negeri dan Upah Minimum terhadap Penyerapan Tenaga Kerja di Indonesia 1990 – 2019 - Widya Putra, Fatah; Ariani, Nani; Nofrian, Fachru (CV. Publikasi Indonesia, 2022)
Absorption of labor is often used as a benchmark for the development of human resources, including the workforce of a country. The minimum wage level of work continues to rise, which can have a positive impact on the workforce, but unlike the company, which sees this as an increase in company costs every year. The aim is to determine the effect of foreign investment, domestic investment, and the minimum wage on employment. Using multiple linear regression analysis methods with OLS. The results of several linear regression analyzes show that foreign investment has a significant effect on employment, domestic investment has no effect on employment, and low state wages have a significant effect on employment. Foreign Investment has an influence and relationship with employment.